Keterlibatan Umat Beriman dalam Karya Misi Gereja Lokal berdasarkan Model Teologi Kontekstual Stephen B. Bevans - Edwind Satri Simatupang (Jurnal Penelitian Pendidikan Agama Katolik, 2023)
The church has a missionary nature. Missionary work is carried out in various ways and its applications. There are many problems that occur, the Church as a missionary is present and participates in solving all the problems that occur. The local church of the Palangka Raya diocese is one of the fields of mission work in spreading the Bible among a pluralistic society. The mission of developing the life of the Catholic faith in Palangka Raya diocese has a long struggle and process. Various methods were used by the missionaries so that salvation did not only occur in certain communities but also among the people living in Central Kalimantan. The establishment of a Pastoral school in the Palangka Raya diocese is one of the efforts to meet the needs of the people and the Church takes part in meeting these needs. This research methodology uses the Research library method. In this study, researchers collected sources from several data documentation from the profile of the Palangka Raya Diocese. Then it is analyzed with Stephen Bevans' mission theology about church missionaries. Based on the analysis, the researcher found that the local Church of the Palangka Raya Diocese was active and participatory in missionary work by missionaries and catechists as a form of faith development.